Interpretative Phenomenological Analysis: Kebahagiaan di Tempat Kerja pada Karyawan di Divisi Sumber Daya Manusia - Desi Wulandri; Megawati Batubara (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2022)
Happiness at work is a positive emotion in a journey to grow and develop so that individuals can maximize performance at work and reach their potential. Happiness at work is a mindset that allows individuals to maximize their potential. This study aims to understand how happiness at work portrays for employees who work in the field of human resources development (HRD). HRD plays an important role in supporting the company's agenda so it is important for the HRD division to manage all human resources in the company so that it runs effectively and efficiently. Three participants in this study were recruited purposively were interviewed using a semi-structured interview. Four quality criteria are used as a form of research credibility. Transcripts were analyzed qualitatively using the interpretative phenomenological analysis (IPA), IPA explores in detail the processes that participants go through to understand their own experiences. Data analysis raises five superordinate themes: (1) employee assessment of the company, (2) satisfaction with the company and the environment, (3) dedication or a sense of company ownership, (4) difficulties faced, (5) resilience. The findings of this study indicate that each participant has difficulties and challenges faced, but how can participants continue to carry out activities despite the difficulties and challenges they face so that individuals can develop by overcoming negative emotions and giving their best ability to help themselves when facing difficulties and challenges.